GE_GERICHTE C/13600/2016 vom 15. September 2017 - GE Cour de justice (2017)
PROTECTION DE L'UNION CONJUGALE ; RELATIONS PERSONNELLES ; OBLIGATION D'ENTRETIEN ; AUDITION DE L'ENFANT | CC.176; CC.276; CC.285; CPC.298.1;